Socialist Realism and orientalism in the novel "The novel of intermounts" by Ivan Le (Literatures of the World: Poetics, Mentality and Spirituality, 2013)
The article is devoted to the study of the eastern images in the «Novel of the in-termountain» by Ivan Le
Keywords: orientalism; social realism